Fuzzy logic-based tuning of PID controller for zeta converter regulation. (July 2020) - Subroto, R K; Ardhenta, L; Hasanah, R N; Sasminto, K
Abstract: In renewable energy, the DC-DC converter plays important roles to convert the electric variables, such as voltage and current. Zeta converter is considered to be widely applied in various applications, includes: power factor correction, photovoltaic generation, and so on. However, the characteristics of the open loop response output voltage from the Zeta converter has quite high overshoot and long settling time. In addition, the input voltage and load variations will affect the Zeta converter's voltage regulation. To encounter these issues, PID controller based on fuzzy logic tuning is implemented to regulate the output voltage of Zeta converter such that the output voltage can follow the desired voltage. According to simulation results the output voltage with fuzzy-PID controlled is able to track the desired reference voltage. Compared to PID controller, the output voltage controlled with fuzzy-PID controller has a smaller voltage deviation and recovery time. At a significant input voltage change the PID controller output response becomes unstable, while the fuzzy-PID controller still produces a good output response.